Direct Visualization of Li Dendrite Effect on LiCoO2 Cathode by In Situ TEM. Issue 52 (6th November 2018) - Yang, Zhenzhong; Ong, Phuong‐Vu; He, Yang; Wang, Le; Bowden, Mark E.; Xu, Wu; Droubay, Timothy C.; Wang, Chongmin; Sushko, Peter V.; Du, Yingge
Abstract: Nonuniform and highly localized Li dendrites are known to cause deleterious and, in many cases, catastrophic effects on the performance of rechargeable Li batteries. However, the mechanisms of cathode failures upon contact with Li metal are far from clear. In this study, using in situ transmission electron microscopy, the interaction of Li metal with well‐defined, epitaxial thin films of LiCoO2, the most widely used cathode material, is directly visualized at an atomic scale. It is shown that a spontaneous and prompt chemical reaction is triggered once Li contact is made, leading to expansion and pulverization of LiCoO2 and ending with the final reaction products of Li2 O and Co metal. A topotactic phase transition is identified close to the reaction front, resulting in the formation of CoO as a metastable intermediate. Dynamic structural and chemical imaging, in combination with ab initio simulations, reveal that a high density of grain and antiphase boundaries is formed at the reaction front, which are critical for enabling the short‐range topotactic reactions and long‐range Li propagation. The fundamental insights are of general importance in mitigating Li dendrites related issues and guiding the design principle for more robust energy materials. Abstract : Using in situ transmission electron microscopy, the atomic level structural and chemical evolutions of LiCoO2 cathode upon Li dendrite contact are directly imaged. It is found that the reaction results in an irreversible conversion of the LiCoO2 cathodes to form Co metal and Li2 O, with CoO as a metastable reaction intermediate.